Mitochondrial genomes of the headstanders Megaleporinus muyscorum (Steindachner 1900) and Megaleporinus obtusidens (Valenciennes 1837), (Characiformes, Anostomidae). Issue 2 (3rd July 2018) - Rincón-Sandoval, Melissa; Betancur-R, Ricardo; Maldonado-Ocampo, Javier A.
Abstract: We report two mitochondrial genomes of headstanders, derived from target capture and Illumina sequencing (HiSeq 2500 PE100). One trans-Andean species Megaleporinus muyscorum (mitochondrial consensus genome of 25 individuals) from Colombia and one cis-Andean species M. obtusidens from Argentina. Regarding M. muyscorum, mitochondrial genome has 13 protein-coding genes, 1 D-loop, 2 ribosomal RNAs, 21 transfer RNAs, and is 14, 434 bp in length, for M. obtusidens mitochondrial genome has 13 protein-coding genes, 2 ribosomal RNAs, 22 transfer RNAs, and is 15, 546 bp in length.